Quark gluon plasma in the early universe expansion with quasi-particle approach. Issue 1 (1st September 2022) - Kumar, Y; Sharma, R; Kuksal, G; Jain, P; Kumar, V; Bangotra, P
Abstract : To understand the behaviour of Quark Gluon Plasma (QGP) in the early stages of universe, a precise temporal evolution of different thermodynamic parameters is studied. Out of many indirect signatures used for the detection of QGP, we compute the Equation of State (EoS) by solving the Friedmann equations. A phenomenological model is used with the value of thermal dependent finite quark mass. The variation of temperature, as well as the energy density with respect to time, are provided which predicts a suitable transition temperature for the phase transition. These results can also be used to calculate other thermodynamic observables. The evolution of early universe and its related properties are thus important in the detection of QGP.